RAPS, Radio Propagation Simulator For CBTC System - Liang, J; Mera, J M; Briso, C; Gómez-Rey, I; Garcerán, A; Maroto, J; Katsuta, K; Inoue, T; Tsutsumi, T (WIT Transactions on the Built Environment, 2012)
CBTC is Communication-Based Train Control system which is a cost-effective solution for signalling and traffic control of metro and monorail. For the CBTC system that can enhance transportation capacity by moving block control method with less trackside equipment, the radio transmission system is one of the most significant subsystems. Especially, the design and location of all radio-electrical elements is the key factor for the system reliability and availability. Therefore RAPS (Radio Propagation Simulator for CBTC Systems) has been developed together with CITEF (Railway Technology Research Centre of the Universidad Politécnica de Madrid), for the purpose of calculating the radio-electrical signal coverage and power along the track, and arranging a proper layout plan of trackside base stations and associated antennas for each project, in consideration of various aspects, such as tunnel geometry, track configuration, environment affecting obstacles. The simulator considers all the characteristics of the trackside, like tunnel detailed geometry, open areas cartography and computes propagation according to the specific radio parameters. RAPS is provided with a complete set of design tools, radio-electrical algorithms such as modal propagation for tunnels and Okumura-Hata and Ray-tracing for open areas providing a high accuracy in the prediction of the signal strength along the track. Also user-friendly graphical